1266 Digital Rectal Examination: Do You Still Put Your Foot in It If You Don't Put Your Finger in It?. (12th October 2021) - Marlow, N; McNamara, J; Ali, R; Bentley, T; James, M; Bond-Smith, G
Abstract: Introduction: Most surgical trainees are familiar with the aphorism 'if you don't put your finger in it, you put your foot in it', with regards to digital rectal examination (DRE). This commonly taught maxim, attributed to Bailey and Love in their Short Practice of Surgery, was coined to highlight the folly of neglecting DRE in patients with histories suggestive of malignant anorectal pathology. However, data are lacking on the diagnostic yield of DRE for detecting anorectal cancer in patients with lower gastrointestinal bleeding (LGIB), whilst advances in biomarker and imaging technology beg the question: is there still a role for DRE in the assessment of patients with LGIB? Method: We designed a clinical coding search strategy to identify all adult patients with acute LGIB referred to general surgery at a UK university hospital from January to July 2020. Electronic patient records were interrogated to identify history and examination findings, diagnoses and clinical outcomes. Results: 169 patients (median age 63 (16-94) years, 54.4% male) were identified, 74.6% (126/169) with bright red bleeding, 23.7% (40/169) with altered blood and 1.8% (3/169) with melaena. DRE was performed in 91.1% (154/169) of patients, identifying blood in 42.9% (66/154) of cases and suspicious lesions, which were subsequently confirmed as anorectal malignancy, in 1.3% (2/154). Conclusions: DRE represents a possibly stigmatising and uncomfortable examination for patients and clinicians alike. These data support the utility of DRE in patients with LGIB and may inform the discussion at the bedside to facilitate the timely diagnosis of anorectal malignancy.